Ultra-High-Molecular-Weight-Polyethylene (UHMWPE) as Desired Polymer Material for Biomedical - Assma Said (Khalij-Libya Journal of Dental and Medical Research, 2021)
It is very important that any materials used as implant material work in harmony with the body. There will be drawback with every material. No matter how good, as nothing can be 100% identical as the natural human tissue. The body operates in an environment at a constant temperature of 37°C and pH of 7.25, so choice of materials will have to withstand these conditions. Incorrect use of material can cause rejection by the body, infection and even cancer, leading to more pain and discomfort by the patient. In turn the possibility of even further damage to the joint. The implant must work in the same way as the body part it is replacing- clear understanding of how the joint works is needed. Ultrahigh molecular weight polyethylene is considered as the standard material for Artificial joints to decrease the total weight and the wear rate to make it more flexible. This is what makes Ultra-High-Molecular-Weight-Polyethylene (UHMWPE) such an appropriate polymer. It is very widely used in total hip and knee joint replacements having the highest known impact strength of any thermoplastic presently made, can highly withstand abrasion, and has a very low coefficient of friction. Therefore, these properties, connected with extremely low moisture absorption, make UHMWPE especial material for the medical industry due to good industrial impact and wear resistance sliding applications. For moving joints, the friction would be damaging without the natural lubrication. In implant components this does not exist, however UHMWPE is self-lubricating, making it ideal for component such as an acetabular cup, which would wrap around a metallic femoral head in a hip joint. Also, UHMWPE has high impact strength, high toughness, and low elastic modulus, but it has disadvantages such as low tensile, transverse and compressive strengths with high creep rate. This review article deals with the history of UHMWPE, its material properties that make it an ideal candidate for total joints, implant-component fabrication procedures and provides insights as to why some of the implants eventually fail.